1987
DOI: 10.1038/clpt.1987.70
|View full text |Cite
|
Sign up to set email alerts
|

Ribavirin disposition in high-risk patients for acquired immunodeficiency syndrome

Abstract: Ribavirin is a broad-spectrum antiviral drug that has in vitro activity against human immunodeficiency virus. To determine the kinetics of ribavirin, 17 symptom-free homosexual men with lymphadenopathy were studied. Single doses of ribavirin, 600, 1200, or 2400 mg, were given orally or intravenously. The plasma ribavirin concentration-time profiles were well fitted by a three-compartment open model. Ribavirin followed linear kinetics over the dose range studied. The mean 1-hour postinfusion concentrations afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
78
1

Year Published

1989
1989
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 0 publications
9
78
1
Order By: Relevance
“…Headache, insomnia, fatigue, and exertional dyspnea have been reported in patients receiving large oral or parenteral doses (10,11,14). These and other observations suggest that ribavirin toxicity is dose related and reversible.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…Headache, insomnia, fatigue, and exertional dyspnea have been reported in patients receiving large oral or parenteral doses (10,11,14). These and other observations suggest that ribavirin toxicity is dose related and reversible.…”
mentioning
confidence: 70%
“…With the second method of elution (three 0.3-ml volumes of 100 mM formic acid), the sensitivity was 0.4 pM in serum, plasma, and cerebrospinal fluid. Because the sensitivity of the HPLC assay is below the therapeutic levels in serum and plasma reported previously for ribavirin (1, 10,14) and because interassay precision was reduced at ribavirin concentrations of less than 0.5 plM, the precision and recovery studies were performed at ribavirin concentrations of between 0.5 and 50 p.M.…”
Section: Resultsmentioning
confidence: 99%
“…We conjecture that decreased early plasma RBV levels in SVRs and enhanced hemoglobin declines early in treatment may reflect higher intracellular RBV concentration in SVRs, although this hypothesis will need to be investigated further. Early studies demonstrated that RBV concentration in erythrocytes can vary from 9 to 60 times more than the plasma concentration following multiple twice daily dosing [26,27]. Higher intracellular RBV concentration may translate into increased mutagenic effect, a proposed mechanism of action for RBV, which may act by lowering HCV infectivity [28] thereby leading to an SVR.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 In contrast to nucleated cells such as hepatocytes, phosphorylation is irreversible in the anucleate erythrocytes, and phosphorylated RBV accumulates because it cannot be exported by the nucleoside carrier. Therefore, the concentration of RBV in erythrocytes is 50-to 70-fold higher than the therapeutic plasma concentration of 9 -15 M. 5,7,8 The high concentration of RBV in erythrocytes is probably responsible for the hemolysis occurring during RBV therapy. A decrease in hemoglobin (HB) is frequently observed in patients who receive RBV, and in one clinical trial this decrease required dose reduction or even treatment discontinuation in 7% of patients.…”
mentioning
confidence: 99%